Teachers, Learners and Edu-Business Co-Constructing Mathematics Curriculum Implementation: An Insider’s Lens in Cross-Phase Longitudinal Research - Jennie Golding (Education Sciences)
This paper draws on a five-component, large-scale, longitudinal and cross-phase mathematics curriculum implementation study in England from the vantage point of an insider to overlapping school, policy and edu-business actor communities. It probed those actors’ emergent co-interpretation of, and response to, a new mathematics curriculum in England, analysing the ways in which edu-businesses, teachers and learners mediate mathematics curriculum policy documents through their own interpretations and schema. The combination of common ‘classroom-close’ research tools supported synergies of cross-phase and longitudinal lenses. The paper contributes an enhanced conceptualisation of inter-actor influence, a theorisation of learner as policy actor, and an understanding of constraints on mathematics policy-driven change at teacher and learner levels, including challenges to communication of intended curriculum policy, across phases of schooling. The approach appears fruitful for analysis of the experience and mediation of mathematics curriculum policy by key policy actors.